Wear behaviour of NiTi shape memory alloys - Yan, Lina (2016)
NiTi shape memory alloys have been widely researched for tribology related applications such as biomedical devices and micro-electro-mechanical system (MEMS) devices. Micro-scale wear is a critical issue in such applications, which may trigger an inflammation of the human body, or result in a malfunction of MEMS devices. Many studies have compared the wear resistance of NiTi SMA with conventional wear resistant materials. However, a systematic study on the wear behaviour of NiTi SMA has rarely being reported. This study aims at understanding the wear behaviour of NiTi SMA, with the hope to provide a guideline for its better use as wear resistant materials. Ball-on-disk sliding wear tests and reciprocating wear tests were conducted, and an alumina (Al2O3) ball was used as counter-body. The effect of major influential factors on the wear behaviour of NiTi SMAs were investigated. Those influential factors including the temperature, applied load, deformation mode, wear cycles, and sliding speed. The deformation mechanisms involved in the wear process were revealed in consideration of the surface wear features, coefficients of friction, stress-strain curves, estimated contact stresses, and microstructures of NiTi SMA. The results can provide guidelines for the effective use of NiTi SMAs as wear resistant materials.